(untitled) (Theatrum historiae, 2013)
The article deals with the attitude of the three most important Czech Churches towards Czech nationalism in the years of the Third Czechoslovak Republic (1945–1948). The Roman Catholic Church repeatedly stood against ill-treatment of Germans or Hungarians. Nevertheless, its criticism of the governmental policy was restrained. The Evangelical Church of Czech Brethren was critically loyal to the state. The Czechoslovak Church supported the governmental policy uncritically. The supranational Roman Catholic Church had to care also for its non-Czech believers. The Evangelical Church of Czech Brethren received into its body also the members of the former German Evangelical Church in Bohemia, Moravia and Silesia. The Czechoslovak Church was a Czech national Church dominated with its pro-communist wing.